2013
DOI: 10.1159/000355245
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Induce Epigenetic Instability through the Formation of 8-Hydroxydeoxyguanosine in Human Hepatocarcinogenesis

Abstract: Chronic hepatitis C (CHC) triggers oxidative stress and contributes to the emergence of hepatocellular carcinoma (HCC). We previously reported that tumor suppressor gene (TSG) methylation is a critical factor during the early stages of hepatocarcinogenesis. In this study, we clarify the association between oxidative stress and epigenetic alterations during hepatocarcinogenesis. We examined DNA oxidation and methylation profiles in 128 liver biopsy samples from CHC patients. The DNA oxidation and methylated TSG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 17 publications
(31 reference statements)
2
75
0
Order By: Relevance
“…Inhibition of natural killer cells or administration of a neutralizing IFN-c antibody inhibits methylation changes, suggesting that natural killer cell function is a key player in inducing aberrant DNA methylation in human hepatocytes after initial HBV and HCV infection [144]. ROS induced by chronic HCV infection could alter histone modification to the repressive form at CpG island-containing tumor suppressor gene promoters, leading to tumor suppressor gene inactivation [145]. These findings suggest that chronic inflammation associated with hepatitis virus infection might cause epigenetic alterations through the immune response as well as through the induction of oxidative stress.…”
Section: Epigenetic Alterations Accumulated In Hepatitis Virus-infectmentioning
confidence: 99%
“…Inhibition of natural killer cells or administration of a neutralizing IFN-c antibody inhibits methylation changes, suggesting that natural killer cell function is a key player in inducing aberrant DNA methylation in human hepatocytes after initial HBV and HCV infection [144]. ROS induced by chronic HCV infection could alter histone modification to the repressive form at CpG island-containing tumor suppressor gene promoters, leading to tumor suppressor gene inactivation [145]. These findings suggest that chronic inflammation associated with hepatitis virus infection might cause epigenetic alterations through the immune response as well as through the induction of oxidative stress.…”
Section: Epigenetic Alterations Accumulated In Hepatitis Virus-infectmentioning
confidence: 99%
“…Gene promoters with 8-OHdG adduct formation have been reported to change the chromatin status from active chromatin with trimethyl-H3K4 and acetylated-H4K16 to a repressive form expressing trimethyl-H3K27 (115). The change in chromatin status was associated with gene methylation.…”
Section: Mechanism: Link Between Oxidative Stress and Epigenetic Genementioning
confidence: 99%
“…3,25 For example, the generation of ROS and 8-OHdG could play a critical role in the abnormal methylation of tumor suppressor genes in the liver of chronic hepatitis C. Nishida et al 3 demonstrated that the 8-OHdG levels were associated with increased numbers of methylated tumor suppressors, and that tumor suppressor genes carrying higher levels of 8-OHdG facilitated the modification of the active chromatin to a repressive form after stimulation by ROS. In addition, the methylation of a tumor suppressor gene, e.g., runt-related transcription factor 3, was significantly increased in bladder cancer cells exposed to H2O2.…”
Section: Discussionmentioning
confidence: 99%
“…2 Growing evidence supports a role for reactive oxygen species (ROS) in epigenetic processes through the generation of oxidative stress. 3 On the other hand, epigenetic processes are also influenced by a variety of dietary antioxidants. For example, maternal dietary antioxidant supplementation mitigated DNA methylation changes in the irradiated offspring.…”
Section: Introductionmentioning
confidence: 99%